Crafting a job in 'tough times': When being proactive is positively related to work attachment. Issue 3 (10th April 2018) - Wang, Hai‐Jiang; Demerouti, Evangelia; Blanc, Pascale Le; Lu, Chang‐Qin
Abstract : Employee work attachment has been found to predict many important work attitudes and behaviours. In this article, we hypothesize that job crafting will be positively associated with work attachment as indicated by psychological ownership of the job and affective organizational commitment. Moreover, drawing on theories and research on work meaning and work identity, we propose that the positive association between job crafting and work attachment will be stronger when employees experience tough times at work (i.e., low‐quality leader‐member dynamics that result from being rated as a poor performer, or experiencing job insecurity). We test our hypotheses in two studies: the first using cross‐sectional survey data from a sample of 295 employees matched with archival performance evaluation data and the second using data collected from two, time‐lagged surveys from a sample of 194 employees and their supervisors. Results from these two studies supported the main effect of job crafting on work attachment. Moreover, the analyses of moderators showed that job crafting was strongly related to work attachment for low performers or insecure job‐holders (i.e., those who experience tough times). The present research provides insights into how to build work attachment by highlighting the proactive role of employees and advances job crafting theory by identifying moderators of job crafting effects. Practitioner points: Employee job crafting is positively related to work attachment (e.g., feelings of job ownership and organizational commitment). Organizations should provide employees with more opportunities to job craft so that employees would get more attached to their work and may thus achieve more positive work outcomes. Low performers and insecure job‐holders develop greater work attachment through job crafting (e.g., seeking more job resources and challenges) than high performers and secure job‐holders.